Ethnographie en période de pandémie et mobilisation des Coronavirus Makers à Barcelone : Le fleurissement des solidarités impromptues - Lambert, Sandrine (Anthropologica, 2023)
On the margins of habitable worlds, impromptu solidarities emerge that restore the potential of a tightly woven humanity, even if it is hanging by no more than a thread. This article is the personal and humorous account of an ethnography in Barcelona where nothing goes as planned, specifically because of a pandemic that fundamentally changes the nature of social interactions. In this chaos, the maker movement that constitutes the object of my research took a spectacular turn, using its 3D printers and its capacity for collective organization and solidarity to manufacture and distribute personal protective equipment that had become impossible to find. Based on interviews and observations, but also articles and grey literature, I analyze the way in which Coronavirus Makers deployed both their power to act and a narrative of the social usefulness of their actions, suddenly very publicized. Thus, in the cracks of a scrambling economy, there were glimpses of the potential to relocalize production based on digital manufacturing, the circular economy, and productive cities. Nevertheless, despite the flamboyance of the epiphany maker, the limits of the liberation of production chains and global supply still very much remain a reality.